PEMBUATAN VIDEO TUTORIAL TEKNIK WINGED EYELINER PADA TATA RIAS WAJAH KOREKTIF UNTUK MATA BULAT (Universitas Negeri Jakarta, 2020)
The purpose of making this video tutorial is to determine the feasibility of video tutorials winged eyeliner technique in corrective makeup for round eyes as an alternative source of learning in the field of beauty, especially in applying makeup. The video production process uses standard operating procedures which are divided into 3 stages, namely the pre-production stage, the production stage, and the post-production stage. Where this research is conducted on a model who has round eyes. The method used in this research is the development method with video assessment by 2 experts, namely the Material Expert and the Media Expert to determine the fesibility of the video tutorial. Based on the feasibility test, the results of the feasibility test of Material Experts were 90% in the very feasible material assessment category and 92% of Media Experts in the media assessment category were very feasible. Based on these results, the video tutorial was declared very suitable for use as an alternative source of learning in the field of beauty in particular. in make-up. Keywords: Video Tutorial, Winged Eyeliner Technique, Eye Corrective Makeup